Effect of Different Annealing Methods on ULTEM 9085 Parts Manufactured by Material Extrusion - Javaid Butt; Habib Afsharnia; Md Ashikul Alam Khan; Vahaj Mohaghegh (Journal of Manufacturing and Materials Processing)
A common practice of improving the performance of parts manufactured by material extrusion is annealing. In this work, ULTEM 9085 parts were subjected to three different annealing methods to compare their effectiveness in terms of dimensional stability, hardness, surface roughness, tensile strength, microstructure and flexural strength. The annealing methods involved heating ULTEM 9085 parts inside an oven in three different ways: direct oven annealing by placing the parts on a tray, fluidized bed annealing with sharp sand surrounding the parts and sandwiching the parts between metal plates. Annealing for all three methods was conducted at temperatures of 180 °C, 190 °C and 200 °C with time intervals of 1 h, 2 h and 3 h. The results showed that direct oven annealing provides consistent results under all scenarios. Better dimensional accuracies were observed with fluidized bed annealing, and metal plate annealing is better suited to ensuring an improved surface finish and higher hardness values. For the tensile test, direct oven annealing yielded the most consistent and optimal results with an increase of up to 28.1% in tensile strength, whereas the other two methods performed better at lower temperatures. Direct oven annealing also led to improved ductility and higher elongation at break. Moreover, microstructural analysis of the fracture surfaces indicated enhanced coalescence for direct oven annealing. In terms of flexural testing, metal plate annealing proved to be more effective, with an increase of up to 13.9% in flexural strength. The other two methods demonstrated consistent results, with direct oven annealing showing slightly higher values compared with unannealed ULTEM 9085 samples. This work provides a useful comparison among different annealing methods that can be used to enhance the performance of ULTEM 9085 parts for different engineering applications.